The complete chloroplast genome sequence of the Alstroemeria hybrid variety ‘Hanhera’ - Jong-Bo Kim; Hwan-Rae Yang; Sang-Hee Lee; Tae-Ho Park (Mitochondrial DNA. Part B. Resources, 2020)
Alstroemeria, a member of the Alstroemeriaceae family, is a species from South America. The chloroplast genome of Alstroemeria spp. was completed by de novo assembly using a small amount of whole genome sequencing data. The chloroplast genome of Alstroemeria spp. was 155,672 bp in length consisting of 84,379 bp of large single copy, 17,815 bp of small single copy, and 26,739 bp of a pair of inverted repeat regions. A total of 157 genes were annotated including 103 protein-coding genes (PCGs), 46 tRNA genes, and eight rRNA genes. Maximum likelihood phylogenetic analysis with seven species belonging to the Alstroemeriaceae or Liliaceae family revealed that Alstroemeria spp. is grouped with the species in the Alstroemeriaceae family.